Pengembangan Media Pembelajaran Berbasis PJBL Pada Mata Pelajaran Akuntansi Perbankan Syariah Kelas XI LPS di SMK - Sari, Eka Dia Permata; Hakim, Luqman (Universitas Hamzanwadi, 2023)
The idea of learning activities, which includes approaches or techniques that have tremendous potential as facilities to support educational activities for students, is a crucial notion. The media serves as a bridge between the teaching and learning processes so that students may grasp the subject matter. This research study aims to develop learning facilities in the form of learning media or learning on a Project Based Learning (PJBL) basis, to assess the viability of Project Based Learning (PJBL) based learning media, and to assess student reactions to learning media on a Project Based Learning (PJBL) basis that was focused on Banking Accounting lessons in class XI and more specifically directed to semester II learning. The ADDIE research approach, which stands for Analysis, Design, proposed by Branch (Development, Implementation, and Evaluation). Students from class XI as Sharia Banking Services (LPS) at SMK Negeri 2 Mojokerto served as the subjects of the media trial in learning activities on a Project Based Learning (PJBL) basis. The study's findings show that project-based learning media receives expert evaluations with a value of 91.5%, which is referred to as the